A Heterozygous Novel Mutation in TFAP2A Gene Causes Atypical Branchio-Oculo-Facial Syndrome With Isolated Coloboma of Choroid: A Case Report - Min, Jie; Mao, Bing; Wang, Yong; He, Xuelian; Gao, Shuyang; Wang, Hairong (Frontiers in Pediatrics, 2020)
Background: Branchio-oculo-facial syndrome (BOFS) is a rare congenital developmental disorder with highly variable clinical phenotypes in autosomal dominant inheritance. The aim of this study is to identify disease-causing mutations in a Chinese family with predominant coloboma of choroid. Case report: We described a family (a mother and her daughter) with unclear clinical diagnosis. The mother (proband) presented with bilateral coloboma of choroid, whereas her daughter had a relatively severe phenotype and presented with larger bilateral choroid coloboma and high-vaulted arch. We applied the next generation sequencing (NGS) panel and analyzed 776 genes related to inherited ocular disorders on the proband. Four candidate heterozygous variants in four genes respectively were detected in the proband. Validation of these variants were subsequently performed in the family using Sanger sequencing. Among these variants, a novel nonsense mutation c.912C>A, p.(Cys304*) (NM_001042425.2) which in exon 6 of the conserved helix-span-helix domain in TFAP2A results in a premature termination codon. It may trigger nonsense-mediated mRNA decay (NMD).Both the affected mother and daughter had this variant, whereas it was absent in the asymptomatic father. Together with the silicon tools and clinical features, we concluded that the variant c.912C>A, p.(Cys304*), was the second reported nonsense mutation in TFAP2A gene, which was the disease-causing mutation of the family. Conclusion: There are many hereditary diseases accompanied by ocular anomalies. For instance, BOFS, patients with atypical features are always at risk of being under-diagnosed. NGS is a powerful method to identify the genetic cause and improve genetic counseling for less clarified hereditary ocular diseases.